Bedside Conventional Tracheostomy in ICU: A Multicenter Experience from Bangladesh - Mazumder, SM Khorshed Alam; Alam, Md Shamsul; Daulatuzzaman, Md; Sikder, Md Ashfaquzzaman; Salam, Md Tahsin; Jahan, Alfatun Akter (Bangladesh Critical Care Journal, 2016)
Tracheostomy is one of the most frequent procedures performed in intensive care unit (ICU) patients. It has many advantages like patients comfort, early movement from the ICU, and shorter ICU and hospital stay. Of the various techniques, we practice bedside open procedure tracheostomy for ICU patients considering the safety and cost effectiveness. Aim: To observe the common indications and timing of tracheostomy in our circumstances. Method: This cross-sectional study was carried out in 11 ICUs of Dhaka city from January 2008 to June 2015. All ICU patients, irrespective of age and sex , whose tracheostomy were done after admission in ICU at bedside by the principal author with associates were included in this study. Result: Bedside conventional tracheostomy was done in 345 ICU patients during the study period. Among them, 65% were male and 35% were female. Mean age of the patients was 44.30. Common indications for tracheostomy were cerebro-vascular disease (36%), laryngeal oedema (20%), advanced malignancy (16%), and trauma (12%). Only 54 patients had complications like hemorrhage (6%), surgical emphysema (3%), tube displacement (3%), wound infection (2%) and pneumothorax (1%). Conclusion: Bedside conventional tracheostomy is safe and efficient with low morbidity. Mortality is not worse and may be improved with earlier provision, especially in head-injured and critically ill medical patients. The timing of tracheostomy continues to be individualized, and should include daily weaning assessment, and can generally be made within 7 days of endotracheal intubation. Bangladesh Crit Care J September 2016; 4 (2): 65-68